Effect of Particle Size on Physicochemical Properties and in vitro Hypoglycemic Ability of Insoluble Dietary Fiber From Corn Bran - Jiang, Caixia; Wang, Rui; Liu, Xiaolan; Wang, Juntong; Zheng, Xiqun; Zuo, Feng (Frontiers in Nutrition, 2022)
This study was designed for determining the effect of particle size on functional properties of corn bran insoluble dietary fiber (IDF). Results showed that some physicochemical properties were improved with the decrescence of particle size. The structure of IDF was observed by the scanning electron microscope (SEM), X-ray diffraction (XRD) and fourier transform infrared spectroscopy (FT-IR). It was found a wrinkled and sparse surface, the particle size became smaller, the crystallini-ty of IDF increased slightly, and more -OH and C-O groups were exposed. Moreover, Corn bran IDF with smaller particle size has better hypogl-ycemic effect in vitro, and the inhibitory activity of α-glucosidase and α-amylase were also increased significantly with the decrease of particle size (p< 0.05). When the IDF was 300 mesh, the inhibitory rate of α-glucosidase was (61.34±1.12)% , and the inhibitory rate of α-amylase was (17.58±0.33)%, increased by 25.54% and 106.83% respectively compaaeed to the control treatment (CK) group. In addition, it was found by correlation analysis that the particle size was highly negatively correlated with some functional properties of IDF (p<0.05), and the content of cellulose was positively correlated with functional properties of IDF except WHC (p<0.05). To sum up, reducing particle size was suitable for the development of IDF high value-added products. This study also revealed the potential value of corn bran IDF, and provided a new idea for the diversified application of IDF.